Reduction of Cracks in Concrete Slabs by Incorporating Synthetic Polypropylene Fiber (Fracture and Structural Integrity, 2025)
In Peru, research on cracking in concrete slabs has been limited, partly due to the perception that cracks do not pose an immediate problem. However, their cumulative effect over the long term can compromise structural durability, highlighting the need for further study. This research was conducted according to the recommendations of ASTM C1579, which establishes procedures for evaluating shrinkage cracking in concrete mixes with and without fiber reinforcement. The main objective was to determine the optimal proportion of polypropylene synthetic fiber that maximizes the reduction in the appearance and formation of cracks. Three dosages were evaluated: DM-01 (500 g/m³), DM-02 (1000 g/m³), and DM-03 (2000 g/m³), compared to a reference concrete (MP) during a 35-day curing period. The results indicated that dosage DM-02 (1000 g/m³) exhibited the best performance, with reductions of 18.41% in average crack thickness, 11.46% in total crack length, and 32.43% in the number of cracks compared to the control concrete. Furthermore, the Mann-Whitney U test applied to DM-02 and MP showed that the average crack thickness at 28 days (p = 0.073) showed a trend toward statistical significance, suggesting a possible reduction in crack thickness with the addition of fibers. In contrast, mixes DM-01 and DM-03 showed heterogeneous results, without substantial improvements in any of the variables; in particular, DM-03 registered an increase in crack thickness. It is concluded that a moderate fiber dosage (DM-02) is the most suitable option, since both a deficiency and an excess of fiber can compromise the material's effectiveness against cracking.
Keywords: Fiber; Concrete; Width; Length; Crack; Polypropylene